Decoding Turkey's Rise: An Introduction - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
Acknowledging Turkey as a rising power, and having commonalities in both objectives and outcomes with the other rising Southern powers, this study is a modest attempt to decode Turkey's rise with/within the West discursively and empirically and at multiple levels: systemic, regional and agent-based domestic. It aims to contribute to the debate over rising powers by developing new conceptualizations and challenging or reinterpreting the existing theoretical approaches in order to define Turkey's current power status vis-a-vis both other rising powers and the major Western powers. Turkey's recent rise, which has also been characterized by the country's high economic growth, must be nuanced from that of the Global South countries in some principal aspects. Unlike other rising powers, the Western factor weights more heavily in Turkey's recent rise. This issue's novel contribution to the existing literature on Turkish foreign policy is its attempt to understand Turkey's current rise, as well as its limitations in the context of its decades-long institutionalized and strategic relations with the West.
Keywords: RISING POWERS; REGIONAL POWERS; STATES; BRAZIL; INDIA